2018
DOI: 10.1016/j.molcel.2018.06.039
|View full text |Cite
|
Sign up to set email alerts
|

ACP Acylation Is an Acetyl-CoA-Dependent Modification Required for Electron Transport Chain Assembly

Abstract: The electron transport chain (ETC) is an important participant in cellular energy conversion, but its biogenesis presents the cell with numerous challenges. To address these complexities, the cell utilizes ETC assembly factors, which include the LYR protein family. Each member of this family interacts with the mitochondrial acyl carrier protein (ACP), the scaffold protein upon which the mitochondrial fatty acid synthesis (mtFAS) pathway builds fatty acyl chains from acetyl-CoA. We demonstrate that the acylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
129
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(142 citation statements)
references
References 49 publications
13
129
0
Order By: Relevance
“…These activated proteins play essential roles in mammals, including as acyl carrier proteins (Praphanphoj et al , ; Donato et al , ). Mitochondrial acyl carrier protein (mtACP), which requires phosphopantetheinyl activation, is essential for electron transport, type II fatty acid synthesis, iron–sulfur cluster biogenesis, and tRNA processing via RNase P (Chuman & Brody, ; Brody et al , ; Autio et al , ; Hiltunen et al , ; Van Vranken et al , , ). Moreover, mtACP is a key factor in coordinating the cellular response to nutrient availability with intermediary metabolism via its requirement for acetyl‐CoA (Hiltunen et al , ; Kursu et al , ; Van Vranken et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…These activated proteins play essential roles in mammals, including as acyl carrier proteins (Praphanphoj et al , ; Donato et al , ). Mitochondrial acyl carrier protein (mtACP), which requires phosphopantetheinyl activation, is essential for electron transport, type II fatty acid synthesis, iron–sulfur cluster biogenesis, and tRNA processing via RNase P (Chuman & Brody, ; Brody et al , ; Autio et al , ; Hiltunen et al , ; Van Vranken et al , , ). Moreover, mtACP is a key factor in coordinating the cellular response to nutrient availability with intermediary metabolism via its requirement for acetyl‐CoA (Hiltunen et al , ; Kursu et al , ; Van Vranken et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…mtACP serves numerous functions that are conserved across species. Indeed, NDUFAB1, the human ortholog of mtACP, is a subunit of and required for the assembly of complex I (Vinothkumar et al, 2014;Van Vranken et al, 2018) and is involved in iron-sulfur biogenesis (Van Vranken et al, 2016). It is possible that the majority of the RNAi-induced phenotype in the Drosophila wing arises from reduced PDH activity and not from other affected processes downstream from holo-mtACP.…”
Section: Discussionmentioning
confidence: 99%
“…Type I animal FASs (including human FAS) terminate synthesis through the action of a thioesterase (TE), releasing the free acid as product. Type II systems in bacteria and mitochondria terminate synthesis through forwarding of acyl‐ACP to lipid biosynthetic pathways, as well as lipoic acid synthesis and electron transport chain (ETC) complex assembly . Type II synthesis in plants is terminated by TE‐mediated hydrolysis…”
Section: Basic Principles Of Fatty Acid Biosynthesismentioning
confidence: 99%
“…Whereas the short‐chain C 8 fatty acids are the precursors of lipoic acid synthesis, the fate of long fatty acids produced in mitochondria is only poorly understood . Recently, it was shown that mitochondrial ACPs carrying long acyl chains are accessory subunits of the ETC complex I …”
Section: The Structure Of Type II Fassmentioning
confidence: 99%
See 1 more Smart Citation